Study on Internal Fatigue Crack Initiation and Propagation Direction of Wind Turbine Gearbox Bearings - Haibo Sun; Feng Shen (Jixie chuandong)
The fatigue crack initiation direction of wind turbine gearbox bearings is investigated. Through theoretical research，it is believed that the direction of crack initiation depends on the direction of the maximum shear stress amplitude plane at the local initiation position. After calculation，it is found that the orthogonal shear stress amplitude of the shallow layer inside the bearing raceway is greater than the principal shear stress amplitude，and the principal shear stress amplitude at the deeper layer is greater than the orthogonal shear stress amplitude. Therefore，the crack initiation angle varies with the initiation depth. Aiming at the problem of crack propagation，the method of stress superposition in the polar coordinate of the crack tip in fracture mechanics is used to clarify the influence of Hertz contact stress，residual stress，assembly interference pressure，etc. on the direction of crack propagation. The applicability of the theory is verified by analyzing the failure cases of bearings with different thermal treatment microstructure.